The Implementation of Anti-Corruption Education through Strengthening Character Values In State Senior High School of North Biak Papua - Patma Tuasikal; Beatus Mendelson Laka (Universitas Sebelas Maret, 2021)
This study aims to determine the implementation of anti-corruption education by strengthening SMA Negeri 1 North Biak's character values. This type of qualitative research used a phenomenological approach to reveal events in the field. The collection technique employed participatory observation, semi-structured interviews, and documentation. Respondents in this study consisted of one school principal and all subject teachers, determined using cluster sampling. Data analysis utilized analysis through data collection, data presentation, data reduction, and conclusion drawing. The results showed that the lack of implementation of anti-corruption education in SMA Negeri 1 North Biak caused students’ characters not to be maximal in three aspects: (1) there is a need for an increase in moral knowledge in independent personality control, (2) there is a need for increased behavior that can increase self-confidence and self-control., and (3) there need to be good role models, both in the school and community environment.